Implementation and Enhancement of Social Media Marketing Strategy on Batam Micro, Small, and Medium Enterprise - Lady Lady; Verren Calystania; Vira Vira; Jessica Novia; Veni Sisca; Stephanie Stephanie (Inovbiz: Jurnal Inovasi Bisnis, 2023)
MSMEs have an essential economic role and contribute significantly to a country's GDP. Over time technology can be used to promote MSMEs by using social media for digital marketing. This study uses De'Sate as its object and a qualitative descriptive approach as its research method. Visits and interviews were carried out with De'Sate owners to obtain the required data. However, it is known that social media hasn’t been utilized optimally. Therefore, this research aims to maximize its digital marketing. Based on the research results, it is known that the business risks are limited employees and less extensive areas. In addition, this study also made changes to the logo, as the font used in the previous logo was less attractive. Next, changes are made to the menu, Instagram feeds and landing page, Google Business, WhatsApp Business catalog and description, auto greeting, quick reply, and away messages on WhatsApp and Facebook Page. A month after the changes, Pak Suryadi was satisfied with the content, and based on the insight of Instagram, performance link, and Google Business, it is known that De'Sate's social media is visited by many users, so it can be concluded that these MSMEs are becoming better known than before.